Prenatal diagnosis of fetal intracranial medulloepithelioma: a case report - Meng, Zhuo; Chen, Lin; Chen, Fangfang; Fu, Shixin; Yu, Hongkui; Chen, Xiaoyan (Frontiers in Neurology, 2024)
Intracranial medulloepithelioma is a very rare and highly malignant tumor that is typically diagnosed in childhood and has an inferior prognosis. In the current report, we described a case of fetal intracranial medulloepithelioma that was detected during the third trimester by prenatal ultrasonography, which displayed homogenous echogenicity with well-circumscribed margins and abundant blood flow. On magnetic resonance imaging, it was hyperintense on both T1- and T2-weighted magnetic resonance imaging. The fetal intracranial tumor was progressive, with rapid expansion within 3 weeks. The report aimed to provide knowledge on the clinical characteristics of fetal intracranial medulloepithelioma in prenatal diagnosis, particularly the radiological features.